REKSA PASTORAL GEREJA DALAM PEMBINAAN MENTAL TNI-POLRI KATOLIK - Agustinus Supriyadi; Andika . (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The Church is sent to continue its mission as to present Jesus Christ throughout its pastoral engineering. By its pastoral engineering, the catholic Church always tries its best to guide all faithful people including those members of the catholic of the Indonesian national army-police. Such pastoral activity should be understood by the catholic of the Indonesian national army-police. Based on the background of study, the study aims to discover how far the members of the catholic of the Indonesian national army-police have understood pastoral engineering of the Church as to improve their mentality and character. To achieve the goal of study, the researcher applied a qualitative method of study. The respondents of study were the catholic of the Indonesian national army-police who live in Mater Dei Parish, Madiun. As a conclusion, the results of study indicated that in general the catholic of the Indonesian national armypolice have not understood well the meaning of pastoral engineering. However, they have participated in any pastoral engineering conducted by Church. The result of the study also indicated that Church has tried its best to develop the catholic of the Indonesian national armypolice mentality. Only a small part of respondents said that Church's concern to improve their spirituality and mentality was still lack. Researcher then suggested catholic spiritual army-police officers have a responsibility to improve a mental and spiritual quality of the catholic of the Indonesian national army-police.